2022
DOI: 10.1007/s10895-021-02866-2
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies and Design of Scrupulous Novel Sensor for Nitro Aromatics Compounds and Metal Ions Detection

Abstract: A Novel Calix[4]pyrrole system bearing carboxylic acid functionality [ABuCP] has been synthesized and its interaction towards various nitroaromatics compounds [NACs] were investigated. ABuCP showed significant color change with 1,3-dinitro benzene (1,3-DNB) in comparison to the solution of other nitroaromatic compounds such as 2,3-dinitro toluene (2,3-DNT), 2,4-dinitro toluene (2,4-DNT), 2,6-dinitro toluene (2,6-DNT), 4-NBB (4-nitrobenzyl bromide) and 4-nitro toluene (4-NT). The ABuCP-1,3-DNB complex produces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…It was observed that the C4P unit in these nanofilms exhibited noteworthy mechanical and separation properties, and hence can play an important role in wastewater treatment. In another study, Fang and teammates also reported robust and defect-free C4P-based nanofilms via dynamic condensation between C4P-tetrahydrzide (98) and aldehyde 97 at the air-DMSO interface (Fig. 15).…”
Section: Polymeric Materials Holding C4p Scaffoldmentioning
confidence: 91%
See 1 more Smart Citation
“…It was observed that the C4P unit in these nanofilms exhibited noteworthy mechanical and separation properties, and hence can play an important role in wastewater treatment. In another study, Fang and teammates also reported robust and defect-free C4P-based nanofilms via dynamic condensation between C4P-tetrahydrzide (98) and aldehyde 97 at the air-DMSO interface (Fig. 15).…”
Section: Polymeric Materials Holding C4p Scaffoldmentioning
confidence: 91%
“…7). 98 According to the experimental studies, they evaluated the sensing potential of 64 towards NACs such as dinitrotoluene (DNT), 4-nitrobenzyl bromide, and 4-nitrotoluene. Receptor 65 acted as a fluorescent sensor, which selectively sensed the Sr 2+ metal ion in the presence of various other competing metal ions such as Mg 2+ , Pb 2+ , Cd 2+ , Pb 2+ , Cr 3+ , and Al 3+ .…”
Section: C4p-based Systems As Sensorsmentioning
confidence: 99%
“…For explosive detection, oxacalixarene can be functionalized with specific chemical groups that interact specifically with nitroaromatic explosives through hydrogen bonding, electrostatic interactions, and van der Waals forces. This interaction can cause a change in the fluorescence or absorption spectra of the oxacalixarene, which can be measured and used to detect the presence of the explosive [15–18] …”
Section: Introductionmentioning
confidence: 99%
“…Pyrene is a polycyclic aromatic hydrocarbon that has a large conjugated pi‐electron system and can undergo pi‐pi stacking interactions with other aromatic molecules, including nitroaromatic explosives. This property makes pyrene a useful fluorescent probe for the detection of explosives [15–18] . Another compound that has been widely explored for the detection of explosives is oxacalix[4]arene, a type of calixarene with a central annulus and upper and lower rims that can be functionalized with different chemical groups to create a highly selective sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation